Stress testing OTC derivatives: Clearing reforms and market frictions - Casu, Barbara; Kalotychou, Elena; Katsoulis, Petros (Journal of Financial Stability, 2025)
We develop a stress-testing network model calibrated to the largest banks and investment funds in over-the-counter (OTC) derivatives markets. We examine the impact of the mandatory collateralisation of bilateral OTC derivatives on liquidity, counterparty, and systemic risks, as well as the impact of market frictions on participants’ ability to withstand liquidity shocks. The collateralisation of bilateral trades reduces counterparty and systemic risks but increases the prominence of liquidity-driven defaults and the potential for the central counterparty to transmit losses. Frictions such as fire sales, delayed payments, and no partial payments by defaulted counterparties greatly increase liquidity risk and systemic losses.